Pembelajaran Bahasa Arab Dalam Buku Ta’lim Al-‘Arabiyah Bi Thoriqoh Haditsah M. Fethullah Gülen - Sholihah, Amaliya; Hidayah, Ihadatul (IAIN Madura, 2020)
The focus of this study is to investigate the thinking of Islamic education figures who have an interest in learning Arabic. This study focuses on a work entitled